2009
DOI: 10.5539/ijbm.v4n8p96
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Efficiency of Malaysian Banks Using Data Envelopment Analysis

Abstract: Data Envelopment Analysis (DEA) Approach is used to estimate the overall, pure technical and scale efficiencies for Malaysian commercial banks during the period 2000-2006. The results suggest that domestic banks were relatively more efficient than foreign banks. Our results also suggest that domestic banks' inefficiency were attributed to pure technical inefficiency rather than scale inefficiency. In contrast, foreign banks inefficiency is attributed to scale inefficiency rather than pure technical inefficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 16 publications
4
32
0
Order By: Relevance
“…It is obvious that most of the foreign banks are relatively inefficient compared to their local counterparts in 2004. This result is consistent with Tahir et al (2009aTahir et al ( , 2009b. Both HSBC and OCBC banks have scored a very low relative technical inefficient in year 2004 mainly due to relatively low pure technical efficiency scores.…”
Section: Results and Discussion Descriptive Statisticssupporting
confidence: 82%
See 3 more Smart Citations
“…It is obvious that most of the foreign banks are relatively inefficient compared to their local counterparts in 2004. This result is consistent with Tahir et al (2009aTahir et al ( , 2009b. Both HSBC and OCBC banks have scored a very low relative technical inefficient in year 2004 mainly due to relatively low pure technical efficiency scores.…”
Section: Results and Discussion Descriptive Statisticssupporting
confidence: 82%
“…This result is consistent with the previous literature, including Sufian (2004), Mohd. Azmi et al (2006), and Tahir et al (2009aTahir et al ( , 2009b. With technological services as inputs, we documented that foreign banks in general are relatively inefficient compared to local Malaysian banks somewhat consistent with Tahir et al (2009aTahir et al ( , 2009b, but after the Malaysia government ended its capital control in 2005, the gap has been gradually closing.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…In the Malaysian banking sector, the DEA approach for measuring the efficiency of a bank was carried out by Tahir et al [14] without incorporating the undesirable output. The study suggested that the domestic banks were relatively more efficient than foreign banks.…”
Section: Literature Reviewmentioning
confidence: 99%